THE STRUGGLE OF HUMAN RIGHTS DIPLOMACY OF INDONESIAN COUNTRY CITIZENS DEATH PENALTY - Robin, Patricia (Dinasti Publisher, 2020)
The ability of politics and diplomacy becomes the main asset when talking about the state. The problem when human rights come against the law, will lead to a tendency to be take the side of the law, as opposed to giving unpleasant things to those who make mistakes. This not infrequently results in the death penalty which eventually (again) contradicts the Human Right to live properly and in protection. This condition occurs in migrant workers who work in several countries in Asia. They were accused of mistakes that incidentally have not been proven but immediately get a death sentence. The best national ambassadors were assigned to conflict areas, succeeded in the mission of saving them. Consistency, innovation, and enrichment when diplomacy is equipped with the ability to read the situation is the key to the success of diplomats when rescuing. Indonesia's ability to maintain good relations with other countries finally deserves to be regarded as the peak of achievement.